Compensation of Subdivision Error of Capacitance Encoder Based on Lissajous Graphic Analysis. Issue 1 (February 2021) - Wang, Aijia; Ding, Hongchang; Hou, Han; Li, Kun; Zhao, Changfu
Abstract: With the development of measurement technology in the direction of precision, high speed, automation, integration, intelligence, economy, non-contact and multifunction, it has simple structure, small size, low energy consumption and strong adaptability. And other advantages have been widely used. However, the sensor of the capacitive encoder works in the state of low voltage and low current, and is extremely susceptible to the influence of the external electric field and magnetic field, causing problems such as input signal distortion and system failure. With the increasing requirements of the manufacturing industry for stability and accuracy, it is of great significance to analyze the capacitive coding error and improve the accuracy. This article analyzes the error generated by the capacitive encoder, enumerates the influence of DC deviation, amplitude deviation, phase deviation, and high-order harmonics on the interpolation error, and compensates the error signal for the aspects that cause larger errors. The sine and cosine signals are close to the ideal state.